Pengaruh Ekstrak Rambut Jagung (Zea mays L.) Terhadap Gambaran Histologi Ginjal Tikus Putih yang Diinduksi Alkohol (Studi in vivo pada Rattus norvegicus) - Yuningtyaswari, Yuningtyaswari; Fitria Hidayati, Ashfi (Green Publisher Indonesia, 2025)
Alcoholic beverages contain ethanol, which is toxic and can increase oxidative stress, potentially damaging the kidneys. Corn silk contains flavonoids with antioxidant effects. This study aims to examine the effect of corn silk extract on the kidney histology of alcohol-induced white rats. This experimental study used a post-test only control group design with 36 rats divided into 9 groups: control (C), negative control (P) receiving 1 ml/day of alcohol, positive control (J1, J2, J3) receiving corn silk extract at doses of 50, 100, and 150 mg/KgBW, treatment groups (PJ1, PJ2, PJ3) induced with alcohol and then given corn silk extract, and the comparator group (S) induced with alcohol and given 1 ml of vitamin C. Kidney histological damage was assessed based on glomerular and tubular damage scores. Data were analyzed using One Way ANOVA and post hoc Duncan tests. The results showed the average kidney damage scores for groups C = 43.35; P = 54.55; J1 = 46.75; J2 = 47.20; J3 = 46.45; PJ1 = 50.75; PJ2 = 46.35; PJ3 = 47.20; and S = 46.90. The glomerular and tubular damage scores of group C differed significantly from P but were not significantly different from other groups. Thus, the administration of corn silk extract (Zea mays L.) does not have a significant effect on the histological appearance of the glomerulus and renal tubules in alcohol-induced white rats (Rattus norvegicus). However, there is a tendency indicating that this extract has the potential to reduce alcohol-induced damage, although the observed differences are not statistically significant.